2014
DOI: 10.1007/s12192-013-0432-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of four heat shock proteins during the aging process in Brachionus calyciflorus (rotifera)

Abstract: Heat shock proteins (HSPs) are molecular chaperones and have an important role in the refolding and degradation of misfolded proteins, and these functions are related to aging. Rotifer is a useful model organism in aging research, owing to small body size (0.1-1 mm), short lifespan (6-14 days), and senescence phenotypes that can be measured relatively easily. Therefore, we used rotifer as a model to determine the role of four typical hsp genes on the aging process in order to provide a better understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 84 publications
2
14
0
Order By: Relevance
“…The critical step is the synchronization of rotifer conditions over several generations. When experimental rotifers are well synchronized, a typical type I survival curve is observed with very little early mortality as reported in several previous studies 18,24,37,38 . Standard deviations of their survival time therefore become smaller compared to poorly synchronized rotifers, resulting in high statistical power.…”
Section: Discussionsupporting
confidence: 77%
“…The critical step is the synchronization of rotifer conditions over several generations. When experimental rotifers are well synchronized, a typical type I survival curve is observed with very little early mortality as reported in several previous studies 18,24,37,38 . Standard deviations of their survival time therefore become smaller compared to poorly synchronized rotifers, resulting in high statistical power.…”
Section: Discussionsupporting
confidence: 77%
“…This observation suggests an interesting hypothesis that treatments shifting metabolism from aerobic to anaerobic pathways could be as effective for life extension as CR. Extending this CR-stress resistance link to B. calyciflorus, Yang et al (2013) showed that CR increased expression of four heat shock genes (hsp 40, 60, 70, 90) and increased rotifer resistance to paraquat-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 97%
“…is a freshwater planarian, characterized by more than a hundred eyes in the head (Aikawa and Shimozawa 1991). Compared with the two most commonly studied species of freshwater planarians, Dugesia japonica and Schmidtea mediterranea, it is more susceptible to various environmental stresses such as temperature variation, heavy metals, and toxic substance pollution; therefore, it is more suitable to be used as test organisms in water environmental toxicology (Li 2008;Knakievicz and Ferreira 2008;Gleixner et al 2014;Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%